1977
DOI: 10.1088/0022-3727/10/4/011
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between sequential dopant diffusions in silicon-a review

Abstract: The trend towards very shallow, submicron diffusion depths in the fabrication of silicon-diffused devices has revealed a number of new diffusion phenomena which form the subject of this review. The diffusion characteristics of some of the individual dopants involved (phosphorus, arsenic, boron and gallium) are first briefly surveyed, and then interactions between sequential diffusions are described in detail.The effects discussed include 'emitter-push' or 'push-out', which is the enhanced penetration of a base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…Influence of phosphorus profile.--It is well known that a phosphorus profile acts as a getter layer during Au-diffusion (5)(6)(7). Moreover, the "emitter push effect" during a phosphorus diffusion has been widely investigated (18,19). While previously this has been explained by the generation of vacancies, Strunk etal.…”
Section: Ocl A2cimentioning
confidence: 99%
“…Influence of phosphorus profile.--It is well known that a phosphorus profile acts as a getter layer during Au-diffusion (5)(6)(7). Moreover, the "emitter push effect" during a phosphorus diffusion has been widely investigated (18,19). While previously this has been explained by the generation of vacancies, Strunk etal.…”
Section: Ocl A2cimentioning
confidence: 99%
“…2, flat-topped profiles of boron are produced through this simulation. Willoughby [9,10] showed that increasing the surface concentration changed the profiles from complementary error function to a flattop shaped. In this simulation, higher concentration of boron was used to match with boron SOD source in laboratory.…”
Section: Resultsmentioning
confidence: 99%
“…This result is in agreement with the conclusions drawn by Claeys et al (1978) and Tseng et al (1978) from differently designed experiments. The emitter-push effect and probably also other anamalous diffusion phenomena of Group I11 and Group V elements in silicon (Willoughby, 1977) are due to supersaturation of Si self-interstitials. The generation of this supersaturation can be understood in terms of a Kirkendall effect for an interstitial-type defect mechanism of diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…The 'emitter-push effect' is one of the closely interrelated anomalous diffusion phenomena of Group I11 and Group V elements in silicon (Willoughby, 1977;Seeger et al, 1979). Its main feature is an extremely rapid diffusion of the base dopant near the emitter region of double diffused npn structures resulting in an enhanced movement of the base-collector boundary below the emitter (Fig.…”
Section: Introductionmentioning
confidence: 99%